217k views
0 votes
For questions 5 – 6, use the following functions:

f(x) = 5x2 + 3
g(x) = x2 - 7
5. Find (f + g)(x).
6. Find (f - g)(x).

For questions 5 – 6, use the following functions: f(x) = 5x2 + 3 g(x) = x2 - 7 5. Find-example-1
User Bazzargh
by
5.0k points

2 Answers

3 votes

Answer:

5.6x2-4

6.4x2+10

Explanation:

User Joeri Sebrechts
by
5.1k points
3 votes

Answer:

5) (f+g)(x) =f(x) +g(x)

[5x^2-3] + [x^2-7]

6x^2 - 4

6) (f -g)(x) = f(x) +g(x)

[5x^2-3] - [x^2-7]

5x^2-3-x^2+7

4x^2+10

User SnuKies
by
5.1k points